Historical Heritage and Ethno-cultural Traditions as a Development Resource of the Tourist Potential of Regions - Bugrov, D. V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2017)
The topic of historical and cultural heritage attracts attention in a variety of spheres, including tourism. Cultural tourism is one of the most popular types of tourism, which includes numerous ways of acquaintance of travellers with the cultural heritage of various cities, regions, and countries. From this perspective, the possibility of using the historical heritage and ethno-cultural traditions of the regions of the Russian Federation provides an important basis for the development of tourism. The paper considers the concept of “cultural tourism” and examines notable examples from the world practice of organising the objects of historical significance. The analysis suggests that the tourist and recreational clusters represent an effective tool for preserving the ways of life and cultural habits of the peoples of Russia. The author points out that a fundamental difference in the views of Russians about interesting and noteworthy sights in their regions of residence exists, and it must be taken into account in the process of the development of the local tourism concepts. Finally, the author points to the key role of the economic and socio-cultural balance in the development of tourism in the regions, as such balance determines the success of efforts to preserve and popularise the local historical and ethno-cultural heritage.